Daya Saing Tanaman Hortikultura di Kabupaten Belu Setelah Fenomena Siklon Tropis - Paebesi, Anselina Dasilva; Nubatonis, Agustinus; Sipayung, Boanerges Putra; Taena, Werenfridus (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This study aims to analyse the competitiveness of horticultural crops in Belu Regency after the tropical cyclone phenomenon. This research method uses descriptive quantitative with Location Quetient analysis, Shift-Share analysis and Panel Data Regression analysis. The results showed that competitiveness experienced a decrease in production during the tropical cyclone period. It can be explained that the decline in production was caused by the tropical cyclone storm which resulted in damage to agricultural crops and agricultural land. As a result, there was a decrease in the production of several types of agricultural products such as horticultural crops. Economic growth, rainfall and temperature have a significant effect on the competitiveness of horticultural crops in Belu Regency.